PENGARUH GAYA BELAJAR DAN PEMANFAATAN MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR EKONOMI PADA SISWA KELAS X SMA N 5 SOLOK SELATAN - Jefri, Jefri; Hia, S.Pd MM, Yulna Dewita; Areva, SPd, Desi (Pendidikan Ekonomi, 2014)
ABSTRACTÂ This research was conducted at SMAN 5 South Solok regarding the influence of emotional intelligence and computer -based media pemanfataan the results belajajar grader sma x 5 South Solok country in economic subjects . The purpose of this study is to obtain empirical evidence about the influence of emotional intelligence and computer -based media pemanfataan the class X results belajajar SMA 5 South Solok in economic subjects .The method used in this research is descriptive and quantitative methods . where the population is students and as many as 182 samples used were as many as 125 students with proportional sampling technique of random sampling . Learning style data ( X1 ) and pemanfataan learning media ( X2 ) is obtained from the results of the questionnaire or the questionnaire while the student learning outcomes data ( Y ) is obtained from the daily student test scores . Analysis of the data used in this study is a descriptive analysis and inductive analysis which consists of classical assumption test , multiple regression analysis and hypothesis testing .The results of this study indicate that : 1 . Learning style significant and positive impact on learning outcomes economy class X SMA Negeri 5 South Solok , 2 . Utilization media student learning positive and significant effect on learning outcomes economy class X SMA Negeri 5 South Solok , 3 . Styles of learning and teaching media pemanfataan simultaneously significant effect on learning outcomes economy class X SMA Negeri 5 South Solok . Based on these results , it is suggested that the school , teachers , and students to pay more attention to students learning styles such as visual learning style , auditory learning styles and learning styles and pemanfataan kirestetik existing instructional media that has been provided by the school in the learning process in an effort to further optimize the learning outcomes of the economy class X SMA Negeri 5 South Solok .